Hubungan Budaya Organisasi Terhadap Inovasi Pendidikan - Junaidi, Roni; Mukhtar, Mukhtar; Anwar, Kasful; MY, Mahmud; Asrulla, Asrulla (IQRO: Journal of Islamic Education, 2024)
Every educational institution, especially Madrasah Aliayah, has its own journey. Just as living creatures go through various phases, such as establishment, revival, and development. There are even private Madrasah Aliyah that eventually dissolve. Organizational culture is one of the significant contributing factors to the progress or decline of educational institutions. The cultural dimension is both abstract and factual, ranging from beliefs, embraced values, basic assumptions, to artifacts. An organization that survives in competition is guaranteed to have a strong organizational culture, whereas stagnant or declining organizations always correlate with weak organizational culture. This not only happens in profit organizations but also in non-profit organizations, including educational institutions. Therefore, building a strong organizational culture is an important agenda for educational institutions. An educational institution with a strong organizational culture will automatically give birth to various contemporary educational innovations as a manifestation of adaptation to the changing times.